2021
DOI: 10.1177/13621688211044238
|View full text |Cite
|
Sign up to set email alerts
|

Exploring fluctuations in the relationship between learners’ positive emotional engagement and their interactional behaviours

Abstract: This study investigated the nature of learners’ positive emotional engagement during a task-based interaction and its relationship with their interactional behaviours. Vietnamese learners of English as a foreign language (EFL; n = 74) performed a communicative task in dyads in 15 minutes. Their positive emotional engagement was gauged using an Experience Sampling Method via a questionnaire that the participants completed after every five-minute interval of the interaction, capturing three timepoints of learner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 96 publications
1
14
0
Order By: Relevance
“…For both modes, task design factors and learner factors seemed to mediate engagement to a moderate extent. Consistent with task-based research (e.g., Aubrey, 2017aAubrey, , 2017bDao & Sato, 2021;Qiu & Lo, 2017), task interest and familiarity played a facilitating role in engagement.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…For both modes, task design factors and learner factors seemed to mediate engagement to a moderate extent. Consistent with task-based research (e.g., Aubrey, 2017aAubrey, , 2017bDao & Sato, 2021;Qiu & Lo, 2017), task interest and familiarity played a facilitating role in engagement.…”
Section: Discussionsupporting
confidence: 75%
“…They found that enjoyment and anxiety were highly dynamic, with patterns of correlation ranging from negative to positive, suggesting that elevated enjoyment occurred during varying levels of anxiety. In a recent classroom-based study, Dao and Sato (2021) measured dynamic affective engagement, operationalized as enjoyment and interest, via a questionnaire at three five-minute intervals during a 15-minute speaking task. They found these measures to increase significantly from the first to second interval, suggesting that, despite using less nuanced measurement methods, affective engagement is still susceptible to considerable change within a task.…”
Section: Language Learner Engagementmentioning
confidence: 99%
“…The idiodynamic measures and postinterviews revealed that learners' motivations and emotions influenced their WTC moment-to-moment and the ways in which they communicated with the conversation partner. Dao and Sato (2021; the current special issue) also identified fluctuations of positive emotional engagement during a 15-minute communicative task. MacIntyre (2020) argued that capturing those 'rapid changes in the psychological conditions' (p. 111) is important to understand both changes in and the stability of communicative processes.…”
Section: Combining Lp and Isla Researchmentioning
confidence: 78%
“…Sato (2017) explored interaction mindset -'a disposition toward the task and/or an interlocutor prior to and/or during the interaction' (p. 250) -and reported that the construct predicted interactional behaviors as well as L2 development. Dao and Sato (2021; the current special issue) operationalized positive emotional engagement as enjoyment and interest, and observed learner interactions. The correlation analyses showed that learners' emotional engagement was related to the amount of L2 production and the degree of collaboration; however, emotional engagement was found to be uncorrelated with the amount of attention to form operationalized as language-related episodes.…”
Section: Volunteer An Answer When the Teacher Asks A Question In Class)mentioning
confidence: 99%
“…Student engagement as a positive variable flourished by PP proponents has been scrutinized in different contexts. Scientific findings have pinpointed that it is positively correlated with effective learning, persistence, retention, motivation, resilience, ambiguity tolerance, agency, willingness to communicate (WTC), and learning perception ( Wimpenny and Savin-Baden, 2013 ; Radmehr and Karami, 2019 ; Dao and Sato, 2021 ; Gu and Sun, 2021 ; Hiver et al, 2021 ; Wind, 2021 ; Zhang, 2021 ). Other than learning benefits, student engagement can meaningfully contribute to students’ socialization, life satisfaction, and psychological well-being ( Trowler and Trowler, 2010 ; Zepke, 2015 ).…”
Section: Introductionmentioning
confidence: 99%